2017
DOI: 10.1186/s12906-017-1684-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and, α-glucosidase inhibitory activities and comprehensive metabolite profiling of methanol extract and its fractions from Clinacanthus nutans

Abstract: BackgroundThis study was aimed to evaluate antioxidant and α-glucosidase inhibitory activity, with a subsequent analysis of total phenolic and total flavonoid content of methanol extract and its derived fractions from Clinacanthus nutans accompanied by comprehensive phytochemical profiling.MethodsLiquid-liquid partition chromatography was used to separate methanolic extract to get hexane, ethyl acetate, butanol and residual aqueous fractions. The total antioxidant activity was determined by 2,2-diphenyl-1-picr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 36 publications
7
36
0
1
Order By: Relevance
“…The phenolic compounds, acting as hydrogen donors, ROS scavengers, and reducing agents, are responsible for many biological activities such as hepatoprotective, anti-allergic, anticancer, anti-inflammatory, antimutagenic, antioxidant, and antidiabetic effects. 35 In the present work, EE had the highest total phenolic content, with 44.42±1.22 mg GAE/g dry weight.…”
Section: Discussionsupporting
confidence: 53%
“…The phenolic compounds, acting as hydrogen donors, ROS scavengers, and reducing agents, are responsible for many biological activities such as hepatoprotective, anti-allergic, anticancer, anti-inflammatory, antimutagenic, antioxidant, and antidiabetic effects. 35 In the present work, EE had the highest total phenolic content, with 44.42±1.22 mg GAE/g dry weight.…”
Section: Discussionsupporting
confidence: 53%
“…(35). In this work, EE had the highest total phenolic content with 44.42 ± 1.22 mg GAE/ g dry weight.…”
Section: Discussionsupporting
confidence: 48%
“…The columns situated opposite to the IC 50 (Y variable) column represent the ions (X variables) that are positively correlated with the activity [11]. The mass spectra of the ions of interest were compared to those in the NIST14 reference library, and only the metabolites with matching index more than 70% were considered [30]. In this study, 16 metabolites were identified to be responsible for the α-glucosidase inhibitory activity ( Figure 5).…”
Section: Putative α-Glucosidase Inhibitory Metabolitesmentioning
confidence: 99%